Large scale genetics of neurodegenerative diseases and ALS - Dupuis, Luc (Henry Stewart Talks, 2024)
Neurodegenerative diseases, Amyotrophic Lateral Sclerosis (ALS), Alzheimer's disease, Parkinson's disease, Fronto-temporal dementia, ALS genetics and risk genes, fALS, TDP-43, FUS, NUP50, UNC13A, Genome-wide association studies, Common and rare genetic variants